Anti-diabetic activity of Allium wallichii on streptozotocin-nicotinamide-induced type-2 diabetes in rat - Vijay Singh Rana; Neeraj Kumar Sethiya; Manmohan Singhal (Bangladesh Pharmacological Society, 2022)
The aim of the present study was to investigate the effect of Allium wallichii leaves extract against streptozotocin-nicotinamide-induced type-2 diabetes in rats. The hydroalcohol extract of A. wallichii leaves (200 and 400 mg/kg) was tested for oral glucose tolerance test and in non-insulin-dependent diabetes mellitus-induced elevated serum glucose levels in the rat. Interestingly, single oral administration of A. wallichii caused a significant (p<0.05) reduction in the serum glucose level (mg/dL). On other hand, A. wallichii normalized plasma glucose levels after repeated oral administration for up to 21 days in diabetic rats (p<0.05). The A. wallichii in the dose of 400 mg/kg showed significant effects on streptozotocin-nicotinamide-induced type-2 non-insulin-dependent diabetes mellitus in rats. In conclusion, therapeutic potential of A. wallichii as per claims is validated towards anti-diabetic potential.